Reacting shock waves characteristics for biogas compared to other gaseous fuel - Abdul Wahid, Mazlan (American Institute of Physics, 2012)
Present article aims to report an experimental study conducted to characterize the reacting shock waves for biogas compared to several other gaseous fuels. A dedicated experimental system which consists of a stainless steel tube with inner diameter of 100mm, a data acquisition system, ignition control unit and gas filling system was built in order to measure the characteristics of high speed reacting shock waves for synthetic biogas such as, pressure history, velocity and cell width. Two types of hydrocarbon fuels were used for comparison in this investigation; propane and natural gas with 92.7% methane. Biogas was synthetically produced by mixing 65% natural gas with 35% carbon dioxide. The oxygen concentration in the oxidizer mixture was diluted with nitrogen gas at various percentage of dilution. Results show that natural gas and biogas were not sensitive to detonation propagation compared to propane. For biogas, methane, and propane it was found that in smooth inner-wall tube, detonation will likely to occur if the percent of dilution gas is not more than approximately 8%, 10% and 35%, respectively. In order to decrease the tube length required for deflagration to detonation transition, an array of obstacles with identical blockage ratio was placed inside the tube near the ignition source. The effect of combustion wave-obstacle interaction was also investigated.